Clinical Evaluation of Giomer and Amalgam Class II Restorations in Primary Molars (Journal of Hama University, 2020)
Purpose: The aim of this study was to compare amalgam and giomer restorative materials in class II restorations in primary molars.Materials and Methods: The research sample consisted of 70 restoration for 70 first or second primary molars in 35 children aged between 5 and 7 years. The sample was divided randomly and equally into two groups according to restoration materials, one of which was restored using giomer and the other was restored using amalgam. The restorations were evaluated after 3, 6, and 9 months.Results: The results showed no statistically significant differences in the marginal discoloration, marginal integrity and secondary caries between amalgam and giomer in class II restorations in primary molars.Conclusion: Giomer can be considered an appropriate alternative for amalgam in class II restorations in primary molars.